Pharmacokinetic Drug‐Drug Interaction Study of Omecamtiv Mecarbil With Amiodarone and Digoxin in Healthy Subjects. Issue 3 (11th October 2021) - Trivedi, Ashit; Sohn, Winnie; Hsu, Cheng‐Pang; Jafarinasabian, Pegah; Zhang, Hanze; Hutton, Shauna; Flach, Stephen; Abbasi, Siddique; Dutta, Sandeep; Lee, Edward
Abstract: Omecamtiv mecarbil (OM), a novel cardiac myosin activator, is being evaluated for the treatment of heart failure with reduced ejection fraction. In vitro studies demonstrate OM as a substrate and inhibitor of P‐glycoprotein (P‐gp), which can result in drug‐drug interactions. Two phase 1, open‐label studies assessed the effect of coadministration of OM (50‐mg single dose) on the pharmacokinetics of digoxin (0.5‐mg single dose; N = 15), a P‐gp substrate, and the effect of coadministration of amiodarone (600‐mg single dose), a P‐gp inhibitor, on the pharmacokinetics of OM (50‐mg single dose; N = 14) in healthy subjects. The ratios of the geometric least squares mean (90% confidence interval [CI]) of digoxin coadministered with OM vs digoxin alone for area under the plasma concentration–time curve (AUC) from time 0 to infinity, AUC from time 0 to the time of the last quantifiable concentration, and maximum observed plasma concentration were 1.06 (90%CI, 0.99‐1.14), 1.06 (90%CI, 0.98‐1.14), and 1.08 (90%CI, 0.92‐1.26), respectively. The ratios of the geometric least squares mean of OM coadministered with amiodarone vs OM alone for AUC from time 0 to infinity, AUC from time 0 to the time of the last quantifiable concentration, and maximum observed plasma concentration were 1.21 (90%CI, 1.08‐1.36), 1.21 (90%CI, 1.07‐1.36), and 1.08 (90%CI, 0.96‐1.22), respectively. In conclusion, OM coadministered with digoxin or amiodarone did not result in any clinically relevant pharmacokinetic drug‐drug interactions.